Examining what best explains corporate credit risk: accounting-based versus market-based models - Trujillo-Ponce, Antonio; Samaniego-Medina, Reyes; Cardone-Riportella, Clara (Journal of Business Economics and Management, 2014)
This paper uses a sample of 2,186 credit default swap spreads quoted in the European market during the period 2002–2009 to empirically analyze which model – accounting- or market-based – better explains corporate credit risk. We find little difference in the explanatory power of these two approaches. Our results indicate that a comprehensive model that combines accounting- and market-based variables is the best option to explain the credit risk, suggesting that both types of data are complementary. We also demonstrate that the explanatory power of credit risk models is particularly strong during periods of high uncertainty, such as those experienced in the recent financial crisis. Finally, the comprehensive model continues to produce the best results if the credit rating is used as the proxy for credit risk; however, accounting variables currently appear to have a more important role than market variables in determining corporate credit ratings.First published online:  05 Feb 2013